Spawning of the Indian major carps in battery of earthen pools - Bandyopadhyay, M K (Indian Journal of Fisheries, 2011)
Further, investigations were initiated on induced spawning of Indian majorcarps {Catla catla, Labeo rohita and Cirrhinus mrigala) enclosed in a batteryof earthen pools consisting of two longitudinally built compartments. A singlesource of continuous water flow was maintained in the earthen pools till thestarting of spawning. The experimental system was designed and operated ina fish farm at Komakantia village, Puri District, Orissa. An attempt was madeto induce spawning of the major carps (Catla catla, Labeo rohita and Cirrhinusmrigala). The experiment was conducted twice during July in 1989 and 1990with a continuous inflow of water to the pools till the starting of spawning.The spawning was totally successful in the injected and non-injected femalesof C. mrigala while it was partial in the case of C. catla and L. rohita